Physical Characterization of Modified Asphalt Binder with Differing Fly Ash Geopolymer Contents - H. Bujang, H. Bujang; M. Y. Aman, M. Y. Aman; T. N. Arumugam, T. N. Arumugam; M. N. M. Taher, M. N. M. Taher (uthm, 2023)
Nowadays, the use of waste material product widely used in the asphalt mixtures industry production due to a cost-effective method of pavement construction that can decrease the consumption of natural resources and to reduce environmental pollution. This research aimed to investigate the possibility of using waste and by-product material namely fly ash geopolymer additive to influence the physical properties of asphalt binder. A series of asphalt binder laboratory tests were carried out to evaluate the properties of the 60/70 and 80/100 asphalt binder incorporating 3%, 5%, 7%, 9% and 11% of fly ash geopolymer additive. The physical properties of the binders were determined using the penetration, softening, penetration index, ductility, and rotational viscosity respectively. The results indicated that, the fly ash geopolymer modified binder had improved the physical properties over base binder. The thermal susceptibility also improved by referring to the Penetration Index value. Overall research conclusions are that geopolymer application resulted in a potential enhancement of some of the properties of the asphalt binder and increase the performance of asphalt binder in the pavement application.